Pengaruh Metode Kombinasi Ceramah, Demonstrasi, Team Game Tournament terhadap Pengetahuan Cuci Tangan pada Remaja di Sekolah Menengah Pertama Negeri di Kota Samarinda - Harfiana, Sendi Sandra Ayu; Asriyadi, Fitroh; Satria, Andri Praja (Poltekkes Kemenkes Palembang, 2025)
Background: Hand washing education is an effort to convey information, skills and understanding to individuals and the community regarding the importance and correct way to maintain hand hygiene with the aim of increasing awareness of the importance of maintaining hand hygiene in preventing the spread of infection. This is also a collective effort to improve habits in society regarding hand washing. The aim of the research was to see the characteristics of respondents based on gender and age, level of knowledge and the influence of the educational methods provided on knowledge. Methods: Quantitative research design using the pre-experimental method Design One Group Pretest- Posttest (initial test-single group final test). The population in this study was 60 people with a total sampling technique. The instruments used were questionnaires and data analysis used. namely the Dependent T-test Results: The research results show that the p value = 0.000 (p < 0.05), this means there is a significant difference between the pre and posttest. It can be concluded that H0 is rejected and Ha fails to be rejected. So there is an influence of the combined educational method on hand washing knowledge in teenagers at SMPN 39 Samarinda. Conclusion: There is an influence between providing combined education on hand washing on knowledge